Gas-Assisted Annular Microsprayer for Sample Preparation for Time-Resolved Cryo-Electron Microscopy - Lu, Zonghuan; Barnard, David; Shaikh, Tanvir R; Meng, Xing; Mannella, Carmen A; Yassin, Aymen; Agrawal, Rajendra; Wagenknecht, Terence; Lu, Toh-Ming (Journal of micromechanics and microengineering, 2014)
Time-resolved cryo electron microscopy (TRCEM) has emerged as a powerful technique for transient structural characterization of isolated biomacromolecular complexes in their native state within the time scale of seconds to milliseconds. For TRCEM sample preparation, microfluidic device [9] has been demonstrated to be a promising approach to facilitate TRCEM biological sample preparation. It is capable of achieving rapidly aqueous sample mixing, controlled reaction incubation, and sample deposition on electron microscopy (EM) grids for rapid freezing. One of the critical challenges is to transfer samples to cryo-EM grids from the microfluidic device. By using microspraying method, the generated droplet size needs to be controlled to facilitate the thin ice film formation on the grid surface for efficient data collection, while not too thin to be dried out before freezing, i.e., optimized mean droplet size needs to be achieved. In this work, we developed a novel monolithic three dimensional (3D) annular gas-assisted microfluidic sprayer using 3D MEMS (MicroElectroMechanical System) fabrication techniques. The microsprayer demonstrated dense and consistent microsprays with average droplet size between 6-9 μm, which fulfilled the above droplet size requirement for TRCEM sample preparation. With droplet density of around 12-18 per grid window (window size is 58×58 μm), and the data collectible thin ice region of >50% total wetted area, we collected ~800-1000 high quality CCD micrographs in a 6-8 hour period of continuous effort. This level of output is comparable to what were routinely achieved using cryo-grids prepared by conventional blotting and manual data collection. In this case, weeks of data collection process with the previous device [9] has shortened to a day or two. And hundreds of microliter of valuable sample consumption can be reduced to only a small fraction.
Keywords: monolithic device; time-resolved TEM; Microfluidics; cryo EM; microspray; micronozzle; microdroplet